Paint recipe book - Wagstaff, Liz (Quadrille Publishing Ltd London, 1998)
The home decorator's bible of achievable paint effects. With step-by-step instructions and close-up swatches showing colour variations, over 150 recipes cover a range of paint finishes for different surfaces. Whether you want a quick, up-to-the-minute makeover on a piece of furniture or to spend time re-creating a period look in your home, the Paint Recipe Book will tell you all you need to know about paint effects and exactly how to achieve them.